Multi-level porous microrods In2O3@C@Ti3C2T for lithium-ion battery anodes x Preparation methods of composite materials
Patent Information
- Application Number
- CN202310865703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-07-14
AI Technical Summary
[0004]为此,本发明所要解决的技术问题在于提供一种用于锂离子电池负极的多级孔微米棒In2O3@C@Ti3C2Tx复合材料的制备方法,以解决现有的多孔结构纳米碳材料制备方法操作繁琐,且制备得到的复合材料用于锂离子电池负极时,储锂容量低、离子传输速率慢以及活性材料容易发生体积变化等问题
[0043]1、采用本发明的方法制备得到的多级孔微米棒In2O3@C@Ti3C2Tx复合材料可以用作锂离子电池负极;其连续的一维多级孔结构具有缩短电子和离子扩散距离、比表面积大、活性位点丰富,以及在循环过程中为体积变化预留空间的优异特性。而且,MIL-68(In)碳化原位形成的碳骨架可以有效缓冲In2O3巨大的体积变化,同时为电子的转移提供高导电性网络。在此基础上,这些相互连接的Ti3C2Tx包裹层在片层孔隙通过双电层电容机制能够吸附和储存更多的锂离子,为内部HPMR-In2O3@C的提供了一个导电的电解质储层。这些结构特征使电极和电解质之间的相互作用更加充分,从而赋予HPMR-In2O3@C@Ti3C2Tx负极更好的循环性能和更优越的倍率性能。
Smart Images

Figure CN116779818B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery anode materials technology. Specifically, it relates to hierarchical porous microrods (In₂O₃@C@Ti₃C₂T) for lithium-ion battery anodes. x Preparation methods of composite materials. Background Technology
[0002] In recent years, the emerging two-dimensional material Ti3C2T x Because of its superior layered structure, metallic conductivity, and abundant functional groups (such as hydroxyl, oxygen, or fluorine groups) and negative charge on its surface, Ti3C2T exhibits great flexibility in interfacial assembly. x As a negative electrode material, Ti3C2T has a low lithium storage capacity. People often refer to it as... x As an additive, it can improve the electrochemical performance of composite materials.
[0003] Carbon materials possess excellent electrical conductivity and structural stability, but their energy density as anodes in lithium-ion batteries is limited. Over the past few decades, researchers have employed various methods to prepare porous carbon nanomaterials to improve lithium storage capacity. These methods primarily utilize conjugated polymers as multifunctional carbon precursors and employ synthesis techniques such as direct template methods, self-assembly methods, template-free methods, chemical activation methods, and microwave stimulation methods to prepare porous carbon nanomaterials. However, these strategies for preparing porous carbon nanomaterials are relatively cumbersome, the resulting anode materials exhibit unsatisfactory charge transfer rates, and the active materials are prone to volume changes during use, leading to a decline in performance. Summary of the Invention
[0004] Therefore, the technical problem to be solved by the present invention is to provide a multi-level porous microrod In2O3@C@Ti3C2T for lithium-ion battery anodes. x The proposed method for preparing composite materials aims to address the problems of cumbersome operation in existing methods for preparing porous carbon nanomaterials, and the low lithium storage capacity, slow ion transport rate, and easy volume changes of active materials when the prepared composite materials are used as negative electrodes in lithium-ion batteries.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0006] Multi-level porous microrods In2O3@C@Ti3C2T for lithium-ion battery anodes x The preparation method of the composite material includes the following steps:
[0007] Step (1): Add indium salt and terephthalic acid to N,N-dimethylformamide and stir to mix well to obtain a homogeneous solution;
[0008] Step (2): Continue heating and maintaining the temperature of the homogeneous solution to obtain mixed reaction system A;
[0009] Step (3): Maintaining the temperature of reaction system A as in step (2), argon gas is introduced into the mixed reaction system A, and Ti3C2T is added dropwise to the mixed reaction system A at the same time. x After the aqueous dispersion is added dropwise, the mixture is kept at a constant temperature. After the reaction is complete, it is allowed to cool naturally to room temperature to obtain mixed reaction system B.
[0010] Step (4): After filtering the mixed reaction system B, the solid product obtained is washed with anhydrous ethanol and then vacuum dried to obtain the precursor MIL-68(In)@Ti3C2T. x ;
[0011] Step (5): Apply the precursor MIL-68(In)@Ti3C2T x The material is placed in a tube furnace and heat-treated under an argon atmosphere. After heat treatment, multi-level porous microrods In2O3@C@Ti3C2T for lithium-ion battery anodes are obtained. x Composite materials.
[0012] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (1), the indium salt is indium nitrate hydrate or indium chloride hydrate; the mass ratio of indium salt to terephthalic acid is 1:2 to 5, the volume mass ratio of N,N-dimethylformamide to terephthalic acid is 90 to 110 mL / g, and the stirring time is 10 to 30 min.
[0013] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of composite materials, step (2) involves heating the homogeneous dispersion to 115-125°C and then holding it at that temperature for 30-40 minutes.
[0014] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (3), the heat preservation temperature is 115-125℃; Ti3C2T x The aqueous dispersion was added dropwise over 5–10 minutes, with an argon gas flow rate of 30–40 mL / min. After the addition was complete, the reaction system contained Ti₃C₂T. x The initial mass ratio of Ti3C2T to the indium salt is 1:9–11; x The mass concentration of the aqueous dispersion is 4–7 wt%; after the addition is complete, continue to keep warm for 30–40 min.
[0015] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (3), Ti3C2T x The preparation of an aqueous dispersion includes the following steps:
[0016] Step (3-1): Add lithium fluoride to hydrochloric acid solution, mix well, and then react. After the reaction is complete, a mixed dispersion A is obtained.
[0017] Step (3-2): Add Ti3AlC2 to the mixed dispersion A in small amounts several times, and continue stirring the reaction. After the stirring reaction is completed, mixed dispersion B is obtained.
[0018] Step (3-3): After repeatedly centrifuging the mixed dispersion B, wash it with ultrapure water until the pH of the washing solution is 6-6.5 to obtain the mixed dispersion C.
[0019] Steps (3-4): After processing, the mixed dispersion C yields Ti3C2T. x Aqueous dispersion.
[0020] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, step (3-4) involves treating the mixed dispersion C to obtain Ti3C2T. x The method for preparing aqueous dispersions is as follows:
[0021] The precipitate obtained after filtering the mixed dispersion C was placed in a vacuum drying oven and dried at 40–45°C for 2–3 hours to obtain Ti3C2T. x Powder; finally, Ti3C2T x The powder is redispersed in water to obtain Ti3C2T. x Aqueous dispersion of Ti3C2T x The aqueous dispersion is a multilayer Ti3C2T x Aqueous dispersion;
[0022] Alternatively, the mixed dispersion C can be repeatedly centrifuged until the upper liquid turns black, yielding mixed dispersion D. Finally, mixed dispersion D is ultrasonicated in an ultrasonic machine with ice packs and then centrifuged. After centrifugation, the upper liquid is taken as Ti3C2T. x Aqueous dispersion of Ti3C2T x The aqueous dispersion is a few-layer / monolayer Ti3C2T xAqueous dispersion; the method of centrifugal expansion is as follows: after each centrifugation, shake the centrifuge tube until the precipitate is redispersed, and then centrifuge again; the centrifugation conditions for centrifugal expansion are 5000–5500 rpm for 1–1.5 min; the ultrasonication time for mixed dispersion D is 30–35 min, and the centrifugation conditions after ultrasonication are 3500–4000 rpm for 15–20 min. Due to the heat generated during ultrasonication, Ti3C2T x It is easily oxidized in aqueous solution and rapidly deteriorates upon contact with oxygen in water at high temperatures. Adding ice packs can prevent Ti3C2T from oxidizing and deteriorating. x Oxidation and deterioration.
[0023] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (3-1), the concentration of the hydrochloric acid solution is 9 mol / L; the molar ratio of lithium fluoride to hydrochloric acid in the hydrochloric acid solution is 1:3; the reaction temperature is 40-45℃ and the reaction time is 15-25 min.
[0024] In step (3-2), the total amount of Ti3AlC2 added is in the molar ratio of lithium fluoride in step (3-1) to 1:11-13; Ti3AlC2 is added in 10-15 portions; the stirring speed during the reaction is 450-550 rpm, the temperature of the reaction is 40-45℃, and the reaction time is 48-50 h.
[0025] In step (3-3), the centrifugation conditions are 3500-4000 rpm for 15-20 min.
[0026] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (4), an organic filter membrane with a pore size of 0.22 μm is used for vacuum filtration, and the membrane is washed with anhydrous ethanol at least 3 times; the vacuum drying temperature is 55-65℃, and the vacuum drying time is 4-5h.
[0027] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, step (5) includes the following two stages of heat treatment:
[0028] Step (5-1): Increase the temperature from room temperature to 120-130℃ at a rate of 4-6℃ / min, and hold for 2-2.5 hours;
[0029] Step (5-2): Continue heating to 500-510℃ at a heating rate of 4-6℃ / min, and hold for 2-2.5 hours. The holding temperature has a significant impact on the product structure and properties. Higher temperatures reduce the degree of graphitization, decrease the amount of dopants, and may even cause the framework structure to collapse. High carbonization temperatures can produce side effects, such as insufficient conductivity and poor crystallinity of the resulting carbon, leading to unsatisfactory applications. The heating rate also significantly affects the product structure and properties; different heating rates result in different product structures and properties. While excessively high heating rates can accelerate the carbonization of organic components, they may also cause the framework to collapse, thereby reducing its surface area and porosity. The heating rate, holding temperature, and holding time set in this invention enable the product to achieve a relatively ideal morphology and specific surface area.
[0030] The above-mentioned hierarchical porous microrods In2O3@C@Ti3C2T used as negative electrodes for lithium-ion batteries x In the preparation method of the composite material, in step (1), the indium salt is indium nitrate pentahydrate, the mass ratio of indium nitrate pentahydrate to terephthalic acid is 1:3, the volume mass ratio of N,N-dimethylformamide to terephthalic acid is 100mL / g, and the stirring time is 20min.
[0031] In step (2), the homogeneous dispersion is heated to 120°C and kept at that temperature for 30 minutes.
[0032] In step (3), Ti3C2T x The aqueous dispersion was added dropwise over 10 minutes, with an argon gas flow rate of 40 mL / min. After the addition was complete, the reaction system contained Ti3C2T. x The initial mass ratio of Ti3C2T to indium nitrate pentahydrate is 1:10; x The aqueous dispersion had a mass concentration of 7 wt%; after the addition was complete, the temperature was maintained at 120°C for 30 min; argon gas was introduced at a specific flow rate as a protective gas to prevent Ti3C2T x It undergoes oxidation and deterioration when exposed to oxygen at high temperatures;
[0033] Ti3C2T x The preparation of an aqueous dispersion includes the following steps:
[0034] Step (3-1): Lithium fluoride is added to the hydrochloric acid solution and mixed thoroughly before reacting. After the reaction is complete, a mixed dispersion A is obtained. The concentration of the hydrochloric acid solution is 9 mol / L. The molar ratio of lithium fluoride to hydrochloric acid in the hydrochloric acid solution is 1:3. Excessive concentration or amount of hydrochloric acid solution may over-etch and damage Ti3C2T. xFor layered structures, if the concentration is too low or the amount used is too small, the etching may be insufficient, resulting in low yield. The reaction temperature is 40℃ and the reaction time is 15min. If the reaction temperature is too high or the reaction time is too long, the hydrochloric acid will volatilize and change its concentration, affecting the etching effect. If the reaction temperature is too low or the reaction time is too short, the etching will be insufficient.
[0035] Step (3-2): Add Ti3AlC2 to the mixed dispersion A in small amounts several times, and continue stirring to react. After the reaction is complete, mixed dispersion B is obtained. The total amount of Ti3AlC2 added is in a molar ratio of 1:12 to the amount of lithium fluoride in step (3-1). If too much Ti3AlC2 is used, the etching may be insufficient, resulting in low yield. If too little is used, it may over-etch and damage Ti3C2. x Layered structure; Ti3AlC2 was added in 15 portions; the stirring rate during the reaction was 500 rpm, the reaction temperature was 45℃, and the reaction time was 48 h. Excessive reaction temperature or reaction time may lead to over-etching and damage of Ti3C2. x The layered structure leads to the formation of the product Ti3C2T. x Oxidative deterioration;
[0036] Step (3-3): After repeatedly centrifuging the mixed dispersion B, wash it with ultrapure water until the pH of the washing solution is 6 to obtain the mixed dispersion C; the centrifugation conditions are 3500 rpm for 15 min; the purpose of washing until the pH of the washing solution is 6 is to separate Ti3C2T x The aqueous dispersion was washed to neutral to remove impurity ions, yielding pure Ti3C2T. x If the aqueous dispersion is not washed thoroughly, the HCl+LiF system will remain and may continue to be etched, resulting in over-etching.
[0037] Steps (3-4): The mixed dispersion C is repeatedly centrifuged until the upper layer turns black, yielding mixed dispersion D. Finally, mixed dispersion D is ultrasonicated in an ultrasonic machine with ice packs and then centrifuged. After centrifugation, the upper layer is taken as Ti3C2T. x Aqueous dispersion; the method of centrifugal expansion is as follows: after each centrifugation, shake the centrifuge tube until the precipitate is redispersed, and then centrifuge again; the centrifugation conditions for centrifugal expansion are 5000 rpm for 1 min; the ultrasonic time for mixed dispersion D is 30 min, and the centrifugation conditions after ultrasonication are 3500 rpm for 15 min.
[0038] In step (4), an organic filter membrane with a pore size of 0.22 μm was used for vacuum filtration, and the membrane was washed three times with anhydrous ethanol. The vacuum drying temperature was 60℃ and the vacuum drying time was 4 h.
[0039] In step (5), the heat treatment includes the following two stages:
[0040] Step (5-1): Increase the temperature from room temperature to 120℃ at a rate of 5℃ / min and hold for 2 hours;
[0041] Step (5-2): Continue heating to 500℃ at a heating rate of 5℃ / min and hold for 2 hours.
[0042] The technical solution of the present invention achieves the following beneficial technical effects:
[0043] 1. Multilevel porous microrods In2O3@C@Ti3C2T prepared by the method of the present invention x Composite materials can be used as anodes in lithium-ion batteries; their continuous one-dimensional hierarchical porous structure possesses excellent properties such as shortened electron and ion diffusion distances, large specific surface area, abundant active sites, and ample space for volume changes during cycling. Furthermore, the in-situ carbon framework formed by the carbonization of MIL-68(In) effectively buffers the large volume changes of In2O3 while providing a highly conductive network for electron transfer. Based on this, these interconnected Ti3C2T... x The coating layer, through its lamellar pores and double-layer capacitance mechanism, can adsorb and store more lithium ions, providing a conductive electrolyte reservoir for the internal HPMR-In2O3@C. These structural features enhance the interaction between the electrode and the electrolyte, thereby endowing HPMR-In2O3@C@Ti3C2T with... x The negative electrode exhibits better cycle performance and superior rate performance.
[0044] 2. This invention combines MIL-68(In) with Ti3C2T x Electrostatic self-assembly, combined with subsequent carbonization treatment, yielded a hierarchical porous microrod indium oxide / carbon / Ti3C2T for use as a negative electrode in lithium-ion batteries. x Composite material (HPMR-In2O3@C@Ti3C2T) x The negative electrode operates at 0.1C (1C = 1000mAh g). -1 Under these conditions, the initial discharge specific capacity is as high as 1406 mAh g. -1 After 249 cycles, the reversible specific capacity reached 1218.7 mAh g. -1 At a current density of 10C, the reversible specific capacity still reaches 214.2 mAh g. -1 It exhibits excellent rate performance. This is achieved by utilizing indium oxide and a carbon framework to form hierarchical porous indium oxide / carbon microrods and Ti3C2T x The dual role of interlayer spacing. Ti3C2T xThe interlayer space can serve as a conductive electrolyte storage layer, promoting more thorough electrochemical reactions during charging and discharging, thus enhancing the performance of HPMR-In2O3@C@Ti3C2T. x It has better cycle performance and rate performance. Attached Figure Description
[0045] Figure 1a SEM images of Ti3AlC2 in embodiments of the present invention;
[0046] Figure 1b In the embodiments of the present invention, multilayer Ti3C2T x SEM image;
[0047] Figure 1c In the embodiments of the present invention, few-layer / monolayer Ti3C2T x Actual photo of the aqueous dispersion;
[0048] Figure 1d In this embodiment of the invention, a single layer of Ti3C2T x AFM diagram;
[0049] Figure 1e In this embodiment of the invention, a single layer of Ti3C2T x Thickness distribution map;
[0050] Figure 1f In the embodiments of the present invention, Ti3AlC2 and multi-layer / monolayer Ti3C2T x XRD pattern;
[0051] Figure 2a TG curve of MIL-68(In) in this embodiment of the invention;
[0052] Figure 2b TG curves of HPMR-In2O3@C in embodiments of the present invention;
[0053] Figures 3a to 3d The respective examples are fl-Ti3C2T from the embodiments of the present invention. x SEM images at 500μm, 100μm, 50μm, and 500nm;
[0054] Figures 3e to 3h The images shown are SEM images of HPMR-In2O3@C at 10μm, 2μm, 500nm, and 500nm, respectively, from the embodiments of the present invention.
[0055] Figures 3i to 3l These are MIL-68(In)@Ti3C2T in the embodiments of the present invention. x SEM images at 10μm, 2μm, 500nm, and 500nm;
[0056] Figures 3m to 3pHPMR-In2O3@C@Ti3C2T in the embodiments of the present invention are respectively x At 10μm,
[0057] SEM images at 2μm, 500nm, and 500nm;
[0058] Figure 4a EDS diagram of HPMR-In2O3@C in the embodiments of the present invention;
[0059] Figure 4b In this embodiment of the invention, MIL-68(In)@Ti3C2T x EDS plot;
[0060] Figure 4c In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x EDS image (10 μm);
[0061] Figure 4d In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x EDS image (1μm);
[0062] Figure 5a TEM image of HPMR-In2O3@C in an embodiment of the present invention;
[0063] Figure 5b HRTEM images of HPMR-In2O3@C in embodiments of the present invention;
[0064] Figure 5c Interplanar spacing diagram of HPMR-In2O3@C in embodiments of the present invention;
[0065] Figure 5d In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x TEM image;
[0066] Figure 5e In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x HRTEM image;
[0067] Figure 5f In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x Interplanar spacing diagram;
[0068] Figure 6 XRD patterns of different materials in the embodiments of the present invention;
[0069] Figure 7a Nitrogen adsorption-desorption curves of different materials in the embodiments of the present invention;
[0070] Figure 7b Pore size distribution diagrams of different materials in embodiments of the present invention;
[0071] Figure 8a In the embodiments of the present invention, fl-Ti3C2T x CV curve;
[0072] Figure 8b CV curves of HPMR-In2O3@C in embodiments of the present invention;
[0073] Figure 8c In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x CV curve;
[0074] Figure 8d In the embodiments of the present invention, fl-Ti3C2T x Charge and discharge curves;
[0075] Figure 8e Charge-discharge curves of HPMR-In2O3@C in embodiments of the present invention;
[0076] Figure 8f In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x Charge and discharge curves;
[0077] Figure 9a Cyclic performance diagrams of different materials in embodiments of the present invention;
[0078] Figure 9b Rate performance diagrams of different materials in embodiments of the present invention;
[0079] Figure 9c In the embodiments of the present invention, Ti3C2T x Impedance diagram;
[0080] Figure 9d Impedance diagram of HPMR-In2O3@C in an embodiment of the present invention;
[0081] Figure 9e In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x Impedance diagram;
[0082] Figure 10a In the embodiments of the present invention, fl-Ti3C2T x Morphology of the electrode before cycling;
[0083] Figure 10b Morphology of HPMR-In2O3@C electrode before cycling in an embodiment of the present invention;
[0084] Figure 10c In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x Morphology of the electrode before cycling;
[0085] Figure 10d In the embodiments of the present invention, fl-Ti3C2T x Morphology of the electrode after cycling;
[0086] Figure 10e Morphology of HPMR-In2O3@C electrode after cycling in an embodiment of the present invention;
[0087] Figure 10f In the embodiments of the present invention, HPMR-In2O3@C@Ti3C2T x Morphology of the electrode after cycling. Detailed Implementation
[0088] 1. Hierarchical porous microrods In2O3@C@Ti3C2T x Preparation of composite materials
[0089] 1.1 Two-dimensional transition metal carbides Ti3C2T x Preparation
[0090] Add 1.56g LiF and 20mL 9mol / L HCl to a 100mL polytetrafluoroethylene (PTFE) reactor and react at 40℃ for 15min. Weigh 1g Ti3AlC2 and slowly add it to the reactor in small increments (15 times). Adjust the reactor speed to 500rpm and react at 45℃ for 48h. After the reaction, pour the slurry into two 50mL centrifuge tubes and centrifuge multiple times with ultrapure water at 3500rpm for 15min until the pH reaches 6. Filter the precipitate using a 0.22μm aqueous filter membrane, dry it, and place it in a 40℃ vacuum drying oven for 2h. After drying, grind it into powder to obtain multilayer Ti3C2T. x Powder (ml-Ti3C2T) x ).
[0091] To obtain few-layer or single-layer Ti3C2T x Powder and improve few-layer or monolayer Ti3C2T x To achieve the desired aqueous dispersion concentration, the solution with a pH of 6 was subjected to centrifugal expansion (centrifugation, hand-shaking the centrifuge tube to disperse the precipitate, followed by centrifugation again) at 5000 rpm for 1 minute, repeated until the upper layer turned black. The centrifuge tube was then placed in an ultrasonicator with ice packs and sonicated for 30 minutes. After sonication, the tube was centrifuged at 3500 rpm for 15 minutes, and the upper black few-layer / monolayer Ti3C2T was collected. x Pour the aqueous dispersion into a beaker; take 1 mL of few-layer / monolayer Ti3C2Tx After the solution is filtered and air-dried for 2 hours, the film is peeled off and weighed to determine whether it is a few-layer or monolayer Ti3C2T film. x Concentration of the aqueous dispersion solution. (This refers to the concentration of a few-layer / monolayer Ti3C2T solution.) x Freeze-drying of aqueous dispersions yields few-layer / monolayer Ti3C2T x powder (fl-Ti3C2T) x ).
[0092] For two-dimensional transition metal carbides Ti3C2T x The structural morphology of the material was characterized, and the results are as follows: Figures 1a to 1f As shown.
[0093] Figure 1a As shown, the original MAX(Ti3AlC2) phase exhibits a dense layered structure with no gaps between the layers. From Figure 1b It can be seen that the two-dimensional transition metal carbides MXenes (Ti3C2T) x The presence of obvious layering and volume expansion indicates that the selective removal of the "A" layer (i.e., Al) from the MAX(Ti3AlC2) phase using the HCl+LiF etching system successfully prepared multilayer MXenes (Ti3C2T...). x This etching method does not require ultrasonic dispersion; it only requires hand-cranking multiple layers of Ti3C2T. x Aqueous dispersions can be used to prepare few-layer / monolayer Ti3C2T x Aqueous dispersion, and Ti3C2T x Fewer defects. Few-layer / single-layer Ti3C2T x It can provide a larger specific surface area and is compatible with multilayer Ti3C2T x Compared to having a larger contact interface, which improves interfacial assembly flexibility and allows for the preparation of better composite materials, MOF materials are relatively sensitive to water. The Ti3C2T obtained by hand-cranking the material... x If the concentration of the aqueous dispersion is too low, excessive water may affect the performance of the composite material in the next step of synthesis. Therefore, we used a centrifugal expansion method to obtain a high dispersion concentration of few-layer / monolayer Ti3C2T. x Aqueous dispersions Figure 1c To reduce the impact of moisture on composite materials and improve their performance, atomic force electron microscopy was used to study few-layer / monolayer Ti3C2T... x Characterization was performed to determine Ti3C2T x The thickness of the slice. Figure 1d and Figure 1e These are atomic force electron microscopy (AFM) images and thickness distribution maps. The AFM images show uniformly sized few-layer / monolayer Ti3C2T. xThe Ti3C2T is densely distributed on the film, and the thickness distribution map shows that it consists of few or single layers. x The thickness of the wafer is around 3nm. Figure 1f Ti3AlC2, ml-Ti3C2T x fl-Ti3C2T x XRD pattern Figures 3a to 3d fl-Ti3C2T x The SEM image shows that after the HCl+LiF etching system etched the Al layer of Ti3AlC2, the 002 peak at 9.44° shifted to the left to 7.62°. This is because the Al layer was etched away, and the insertion of water molecules caused the Ti3C2T peak to shift to the left. x The lattice spacing was increased by Bragg's equation, and the interlayer spacing was calculated to have increased from 0.93 nm to 1.16 nm. (Ti3C2T) x The residual weak peak at 9.44° indicates that the etching was insufficient and a small amount of Ti3AlC2 is still present.
[0094] 1.2 Hierarchical porous microrods In2O3@C@Ti3C2T x Preparation of composite materials
[0095] (1) Take 1g of In(NO3)3·5H2O and 3g of PTA into a 500mL round-bottom flask, add 300mL of N,N-dimethylformamide (DMF), transfer to an oil bath and stir rapidly for 20min to form a homogeneous solution; heat the homogeneous solution to 120℃ and continue heating and stirring for 1h; after the reaction is completed, let it cool naturally to room temperature, filter it with an organic filter membrane of 0.22μm, and wash it 3 times with anhydrous ethanol; after washing, dry it in a forced-air drying oven at 60℃ for 4 hours to obtain the precursor MIL-68(In) powder.
[0096] (2) The above-mentioned precursor MIL-68(In) was placed in a tube furnace and heated from room temperature to 120°C for 2 hours under an argon atmosphere at a heating rate of 5°C / min. This process mainly removes water and unreacted DMF. The temperature was then increased to 500°C at a heating rate of 5°C / min and held for 2 hours to carbonize the organic framework and prepare hierarchical porous indium oxide / carbon microrods (HPMR-In2O3@C).
[0097] (3) Take 1g of In(NO3)3·5H2O and 3g of PTA respectively and put them into a 500mL three-necked round-bottom flask. Add 300mL of N,N-dimethylformamide (DMF) and transfer it to an oil bath. Stir rapidly for 20min to form a homogeneous solution. After the homogeneous solution is formed, heat it to 120℃ and keep it at that temperature for 30min. Use one end to pass high-purity argon gas (argon gas flow rate of 40mL / min), one end to discharge waste gas, and one end to add Ti3C2T dropwise. x Aqueous dispersion, added dropwise to Ti3C2T x The mass reaches 0.1g, and the temperature is maintained for another 30 minutes. Ti3C2T x The aqueous dispersion was added dropwise over 10 minutes, Ti3C2T x The aqueous dispersion had a mass concentration of 7 wt%. After the reaction was complete, the mixture was allowed to cool naturally to room temperature and then filtered through a 0.22-micron organic filter membrane. It was then washed three times with anhydrous ethanol. After washing, the mixture was vacuum-dried at 60°C for 4 hours in a vacuum drying oven to obtain the precursor MIL-68(In)@Ti3C2T. x The aforementioned precursor MIL-68(In)@Ti3C2T x The sample was placed in a tube furnace and heated from room temperature to 120°C at a heating rate of 5°C / min under an argon atmosphere, and held for 2 hours. The temperature was then further increased to 500°C at a heating rate of 5°C / min and held for 2 hours to prepare a hierarchical porous indium oxide / carbon / Ti3C2T. x Microrods (HPMR-In2O3@C@Ti3C2T) x ).
[0098] (4) As a control, the prepared few-layer / monolayer Ti3C2T was prepared by freeze-drying. x Freeze-drying of aqueous dispersions to obtain few-layer / monolayer Ti3C2T with ultra-long flake diameters x Powder (i.e., the fl-Ti3C2T prepared above) x ), to prevent Ti3C2T x The pieces were re-stashed.
[0099] 2. Differential thermal and thermogravimetric analysis of materials
[0100] Thermogravimetric analysis (TG or TGA) was performed using a STA449F3 Jupiter thermogravimetric analyzer manufactured by Netzsch GmbH, Germany. The test temperature ranges were 20–400℃ and 20–700℃, with a heating rate of 10℃ / min. The samples were tested in oxygen and nitrogen atmospheres.
[0101] like Figure 2aAs shown, two distinct weight loss stages are clearly visible. The first weight loss occurred within the temperature range of 110-346℃, resulting in a 22% loss, primarily due to physically absorbed water and a small amount of unreacted DMF. The second weight loss occurred between 346-500℃, mainly due to the oxidative decomposition of the MOF framework, resulting in a 26% loss. Above 500℃, the weight loss showed almost no fluctuation, indicating that the MIL-68(In) precursor was completely converted to HPMR-In2O3@C. Therefore, the optimal carbonization temperature for the obtained sample should be 500℃. To determine the carbon content percentage in the HPMR-In2O3@C composite material, thermogravimetric analysis (TGA) was performed on HPMR-In2O3@C under an oxygen atmosphere. Figure 2b As shown in the figure, there is a slight weight gain before 285℃, which may be due to the oxidation of a small amount of indium metal generated during the reduction process, forming indium oxide. Weight loss begins at 285℃ and stops at 488℃; the 22% loss is due to the complete oxidation of carbon into CO and CO2. Therefore, the carbon content in HPMR-In2O3@C is 22% by mass.
[0102] 3. Structural morphology characterization of materials
[0103] The X-ray diffraction (XRD) test used a Rigaku Ultima IV XRD instrument manufactured in Japan, with a testing range of 5–90° and a scanning rate of 5° / min in continuous scanning mode. A Cu target and a high-sensitivity D / teX Ultra250 detection system were employed. The crystal structure of the material was analyzed using XRD. The scanning electron microscope (SEM) used was a Czech-made TESCANMIRA LMS. The microstructure and structure of the material were analyzed using SEM. The transmission electron microscope (TEM) used was a Japanese-made JEOL JEM-2100F. X-ray fluorescence spectrometry (XRF) uses physical principles to detect the elements in a substance, enabling qualitative and quantitative analysis. Specifically, X-rays penetrate the electrons inside atoms, and the outer electrons replenish the characteristic X-rays, allowing for the determination of the elemental composition based on the intensity of these characteristic X-rays. The X-ray fluorescence spectrometer used was a Rigaku ZSX PrimusIII+. The nitrogen adsorption-desorption analyzer utilizes the adsorption and desorption properties of N2 on the sample surface to obtain the material's specific surface area, pore volume, and pore size distribution. The nitrogen adsorption-desorption analyzer used was a Micron ASAP2460.
[0104] Figures 3a to 3d fl-Ti3C2T x SEM image of fl-Ti3C2T x It exhibits a single-layer structure with an extremely large flake diameter and a smooth surface. The scanning electron microscope image of HPMR-In2O3@C is shown below. Figures 3e to 3h As shown, the morphology reveals the process of MIL-68(In) derivation into HPMR-In2O3@C. MIL-68(In) is carbonized in an inert atmosphere, and the In in the MIL-68(In) precursor... + The organic framework is transformed into In2O3 nanocrystals. Through thermal polymerization, it forms a cross-linked carbon network, which is then carbonized into a skeleton that combines with the In2O3 nanocrystals to form porous indium oxide / carbon microrods (HPMR-In2O3@C) with an average width of approximately 1.44 μm. These HPMR-In2O3@C microrods exhibit a compact structure, and numerous nanoparticles can be clearly observed growing uniformly on their surface. We attribute this distribution of In2O3 nanoparticles to the generation of water vapor and organic vapors by the organic components at high temperatures during the pyrolysis of MIL-68(In). As these gases diffuse out, the In2O3 crystal nuclei migrate towards the surface of the microrods, ultimately transforming into In2O3 nanoparticles with a small particle size. Furthermore, the microrods exhibit highly uniform shape and size, possessing a good specific surface area. Figures 3i to 3l MIL-68(In)@Ti3C2T x The SEM image clearly shows the compact, smooth surface of the rod-like MIL-68(In) structure; simultaneously, the rod-like MIL-68(In) structure is similar to the layered Ti3C2T structure. x They are intertwined. The results show that Ti3C2T x The electrostatic self-assembly does not affect the formation of MIL-68(In), and Ti3C2T x MIL-68(In) was successfully electrostatically self-assembled with Ti3C2T to form MIL-68(In)@Ti3C2T x Composite materials. Figures 3m to 3p MIL-68(In)@Ti3C2T x Derived HPMR-In2O3@C@Ti3C2T x SEM image of the composite material. The image shows that the rod-like structures are interwoven in a lamellar structure. The results indicate that MIL-68(In)@Ti3C2T x At an annealing temperature of 500℃, hierarchical porous indium oxide / carbon / MXenes (Ti3C2T) can be generated in situ. x Micrometer rods (HPMR-In2O3@C@Ti3C2T)x These images show that the R-In2O3@C@Ti3C2T synthesized through thermal treatment... x The composite material largely retains the properties of MIL-68(In) / Ti3C2T x The structure of the precursor can also be observed. HPMR-In2O3@C@Ti3C2T can also be seen. x Compared to HPMR-In2O3@C, the surface is smoother, indicating that HPMR-In2O3@C@Ti3C2T x It is a core-shell structure, with layers of Ti3C2T x A coating layer was formed on HPMR-In2O3@C. Figures 4a to 4c HPMR-In2O3@C, MIL-68(In)@Ti3C2T x and HPMR-In2O3@C@Ti3C2T x EDS plot, Figure 4a The coexistence of C, O, and In elements in HPMR-In2O3@C was shown, confirming that In2O3 is bonded to the carbon framework. Figure 4b MIL-68(In)@Ti3C2T was displayed. x The elemental distribution of C, In, O, and Ti in the sample confirms that MIL-68(In) undergoes electrostatic self-assembly with Ti3C2T. x Intertwined. Figure 4c HPMR-In2O3@C@Ti3C2T was shown. x The elemental distribution of C, In, O, and Ti in MIL-68(In)@Ti3C2T is used to prove the properties of the molecule. x In-situ carbonization of MIL-68(In) occurred, forming HPMR-In2O3@C@Ti3C2T x .
[0105] Figures 5a to 5c The structural characteristics of HPMR-In2O3@C are clearly shown. Amorphous carbon formed by the carbonization of the organic framework is combined with In2O3. The interplanar spacing of the nanoparticles is measured to be 0.292 nm, which coincides with the (222) plane of In2O3. The above results indicate that the carbon framework is combined with the In2O3 nanoparticles. Figures 5d to 5f HPMR-In2O3@C@Ti3C2T was clearly shown. x Structural characteristics of Ti3C2T x A coating layer was formed on the rod-shaped HPMR-In2O3@C structure. Through... Figure 5e Interplanar spacing was measured at the In2O3 position, and the interplanar spacing at 0.413 nm coincided with the (2 1 1) plane of In2O3; Figure 5eTi3C2T x At this location, atoms were observed to be arranged in a hexagonal pattern, with a lattice spacing of approximately [missing information]. It can be attributed to Ti3C2T x (1 00) plane (space group: P63 / mmc, This proves that Ti3C2T x The reconciliation was successful.
[0106] Figure 6 fl-Ti3C2T x HPMR-In2O3@C and HPMR-In2O3@C@Ti3C2T x The XRD patterns are shown in the figure. The HPMR-In2O3@C composite material and the HPMR-In2O3@C@Ti3C2T composite material are also shown. x The XRD patterns of the composite materials show deep overlap. HPMR-In₂O₃@C, HPMR-In₂O₃@C@Ti₃C₂T x The diffraction peaks at approximately 21.5°, 30.6°, 35.5°, 45.7°, and 51.3° all belong to In₂O₃, indicating the presence of In₂O₃ crystals in the composite material. This suggests that the precursor MIL-68(In) generates hierarchical porous In₂O₃ / C microrods (HPMR-In₂O₃@C) by high-temperature carbonization of the organic framework under an argon atmosphere. However, no diffraction peaks of crystalline carbon were observed; therefore, the carbon in the sample is amorphous. HPMR-In₂O₃@C and HPMR-In₂O₃@C@Ti₃C₂T x The diffraction peak at approximately 32.9° of the composite material corresponds to that of metallic indium. This is because a small amount of indium oxide in the composite material was reduced to metallic indium by carbon at high temperature. HPMR-In₂O₃@C@Ti₃C₂T x Compared to HPMR-In2O3@C, Ti3C2T can be observed. x The classic 002 peak indicates that Ti3C2T x The composite was successfully achieved. Furthermore, HPMR-In2O3@C@Ti3C2T x The In2O3 diffraction peak intensity of Ti3C2T is lower than that of HPMR-In2O3@C, indicating that Ti3C2T x Electrostatic self-assembly was performed with MIL-68(In) Ti3C2T x A Ti3C2T layer was formed on the surface of MIL-68(In). x The shell, after subsequent carbonization, is Ti3C2T. xThe coated MIL-68(In) is generated in situ as HPMR-In2O3@C, thus forming a core-shell composite material HPMR-In2O3@C@Ti3C2T. x .
[0107] Table 1 Elemental Content Table
[0108]
[0109] To determine HPMR-In2O3@C@Ti3C2T x The content ratio of Ti to In in the sample was determined by X-ray fluorescence spectrometry (XRF) using HPMR-In₂O₃@C@Ti₃C₂T. x The tests were conducted and are shown in Table 1, yielding R-In2O3@C@Ti3C2T. x The ratio of Ti to In in the sample was 19.3 / 80.7.
[0110] Specific surface area and pore size distribution have a significant impact on electrochemical behavior. Figures 7a to 7b Table 2 shows the isothermal nitrogen adsorption-desorption curves and pore size distribution curves for fl-Ti3C2T, respectively. x , HPMR-In2O3@C, HPMR-In2O3@C@Ti3C2T x Specific surface area and pore volume table. Among them, sample fl-Ti3C2T x Its specific surface area is 12.1230 m². 2 / g, the nitrogen adsorption-desorption curves exhibit typical Type III isotherms for non-porous or macroporous solid materials; fl-Ti3C2T x The total pore volume is 0.01890 cm³. 3 / g, judging from the pore size distribution curve, fl-Ti3C2T x Almost no pore structure is present; these data are consistent with the morphology characterized by SEM, fl-Ti3C2T x It exhibits a layered structure without pores. The specific surface area of the MIL-68(In) derived HPMR-In2O3@C material is 269.8704 m². 2 The nitrogen adsorption isotherm of this sample exhibits a type IV isotherm with a distinct hysteresis loop, indicating the presence of a mesoporous structure. Rapid N2 absorption in the low-pressure region (P / P0~0) suggests the presence of numerous micropores. The total pore volume of HPMR-In2O3@C is 0.481170 cm³. 3The pore size distribution, assessed by Barrett-Joyner-Halenda (BJH), shows that the pore size ranges from 2 nm to 100 nm, with the highest concentration of mesopores smaller than 10 nm. This hierarchical porous structure promotes contact between the electrolyte and the electrode, shortens the lithium-ion diffusion path, and improves charge conduction rate. The gas generated during the carbonization of MIL-68(In) escapes from the interior, contributing to the formation of the porous properties of HPMR-In2O3@C. The larger BET surface area and hierarchical pore size distribution provide more active reaction sites, thereby improving the battery's specific capacity and cycle stability. Figure 7a As shown, the sample HPMR-In2O3@C@Ti3C2T x The nitrogen adsorption-desorption isotherm curve is type IV, exhibiting a significant hysteresis loop, indicating the presence of a mesoporous structure. Rapid N2 absorption in the low-pressure region (P / P0~0) indicates the presence of numerous micropores. Pore size distribution analysis by Barrett-Joyner-Halenda (BJH) shows that pore sizes range from 2 nm to 100 nm, with the highest concentration of mesopores smaller than 10 nm. This hierarchical porous structure offers advantages such as increased active sites, improved electrolyte-electrode contact, and shortened lithium-ion diffusion paths. It can promote electrolyte-electrode contact. HPMR-In2O3@C@Ti3C2T x The specific surface area is 241.1755 m². 2 / g, total pore volume is 0.396742cm³ 3 / g, the specific surface area is slightly lower than that of HPMR-In2O3@C, because Ti3C2T x The near absence of micropores and low specific surface area reduce the number of micropores in the composite material to some extent, thus lowering the specific surface area. However, the pore size distribution curve shows that although Ti3C2T... x The number of micropores was reduced, but the number of mesopores and macropores in the 11-100 nm range was significantly increased. This makes HPMR-In2O3@C@Ti3C2T x This allows for better utilization of the advantages of hierarchical pores: macropores can serve as electrolyte storage tanks, mesopores as mass transfer channels, and micropores to provide electrochemical active sites. Ti3C2T x The interlayer space can serve as a storage layer for electrolytes, promoting more thorough electrochemical reactions during charging and discharging.
[0111] Table 2 Specific surface area and pore volume
[0112]
[0113] fl-Ti3C2Tx , HPMR-In2O3@C, HPMR-In2O3@C@Ti3C2T x The CV curve is as follows Figures 8a to 8f As shown. Figure 8a fl-Ti3C2T x The CV curves show a distinct reduction peak (0.66 V) in the first cycle, which then disappears in subsequent cycles. This irreversible reduction peak near 0.66 V is likely attributed to the formation of a solid electrolyte interphase (SEI) film primarily composed of lithium carbonate and alkyl lithium components. This corresponds to... Figure 8d The charge-discharge curves show a significant long discharge plateau during the first discharge, indicating a substantial decrease in specific capacity after the first charge-discharge cycle. This is because the initial charge-discharge cycle forms an SEI film, resulting in a relatively high irreversible specific capacity. The CV curves for the second and third cycles are essentially identical, with no obvious lithiation or delithiation peaks, indicating stronger capacitance performance. The corresponding charge-discharge curves for the second and third cycles are also essentially consistent, suggesting that after the irreversible reaction in the first cycle, the reaction between the electrode and the electrolyte approaches stability. Figure 8b The CV curve for HPMR-In₂O₃@C shows a distinct irreversible reduction peak (0.61 V) in the first cycle, which disappears in subsequent cycles. This is because HPMR-In₂O₃@C possesses a well-developed porous structure and a large specific surface area. When the active material contacts the electrolyte, a large amount of solid electrolyte interphase (SEI) film composed of lithium carbonate and alkyl lithium components is formed. Simultaneously, a Li-ln alloy is formed during the multi-step electrochemical reduction reaction between In₂O₃ and Li. This corresponds to... Figure 8e The charge-discharge curves show a significant ultra-long discharge plateau between 0.5V and 0.8V during the first discharge, indicating a substantial decrease in specific capacity after the initial charge-discharge cycle. This is attributed to the formation of a large amount of SEI film during the charge-discharge process, resulting in a relatively high irreversible specific capacity. In the second cycle, the appearance of three oxidation peaks (0.42V, 0.69V, 1.72V) and three reduction peaks (0.40V, 0.53V, 0.65V) indicates multi-step electrochemical reactions related to the lithium delithiation / intercalation process, corresponding to... Figure 8eThe charge-discharge curves show distinct charging plateaus near 0.42V, 0.69V, and 1.72V, and distinct discharging plateaus near 0.40V, 0.53V, and 0.65V. In subsequent cycles, the reduction peak at 0.65V shifted to 0.59V in the third cycle, likely due to the largely irreversible reduction of In₂O₃ to metallic In. The CV curves for the second and third cycles are essentially identical, indicating that the electrode-electrolyte reaction is nearly stable after these irreversible reactions. The corresponding charge-discharge curves also show similarities between the second and third cycles, with minimal capacity decay. This is closely related to the bonding of In₂O₃ with carbon. The In₂O₃ nanoparticles are well integrated with the carbon framework, not only increasing charge transport but also buffering the volume changes of In₂O₃ during redox reactions. Figure 8c HPMR-In2O3@C@Ti3C2T x The CV curves showed a sharp, irreversible reduction peak (0.66 V) in the first cycle, which disappeared in subsequent cycles. This is attributed to the decomposition of the organic framework, which caused the HPMR-In2O3@C@Ti3C2T x The hierarchical porous structure and high specific surface area lead to the formation of a large amount of solid electrolyte interphase (SEI) film composed of lithium carbonate and alkyl lithium components. Simultaneously, a Liln alloy is formed during the multi-step electrochemical reduction reaction of In₂O₃ and Li. Correspondingly, in... Figure 8f The charge-discharge curves show a significant ultra-long discharge plateau between 0.66V and 0.82V during the first discharge, indicating a substantial decrease in specific capacity after the first charge-discharge cycle. This is attributed to the formation of a large SEI film during the first charge-discharge process, resulting in a relatively high irreversible specific capacity. The graph also shows that the CV curves for the second and third cycles are essentially identical, corresponding to the similarity between the charge-discharge curves for the second and third cycles. This indicates that after the irreversible reaction in the first cycle, the reaction between the electrode and the electrolyte approaches stability. In the second cycle, three oxidation peaks (0.43V, 0.70V, 1.74V) and three reduction peaks (0.43V, 0.51V, 0.79V) indicate multi-step electrochemical reactions related to the lithium delithiation / intercalation process. Figure 8f The charge-discharge curves show distinct charging plateaus near 0.43V, 0.70V, and 1.74V, and distinct discharge plateaus near 0.43V, 0.51V, and 0.79V. In the third cycle, the reduction peak at 0.79V, present in the second cycle, nearly disappears, likely due to the largely irreversible reduction of In₂O₃ to metallic In. The CV curves show that HPMR-In₂O₃@C@Ti₃C₂T xThe reduction peak intensity in the 0.01V-0.2V range is sharper than that of HPMR-In2O3@C, which is attributed to the lithium in Ti3C2T x Layer insertion. Simultaneously, Ti3C2T x Electrolytes can be stored between layers, promoting more complete electrochemical reactions during charge and discharge. Based on these CV curves, it can be concluded that alloying and dealloying are the main lithium storage mechanisms during charge and discharge.
[0114] Figure 9a Different negative electrode sheets and lithium sheets were assembled into half-cells at 0.1C (1C = 1000mAh g). -1 The cyclic performance graph measured at the rate of ) shows that in the first cycle, fl-Ti3C2T x The discharge specific capacity of the negative electrode is 84.8 mAh g. -1 The second cycle fl-Ti3C2T x The discharge specific capacity of the negative electrode is 51.4 mAh g. -1 The decrease in discharge specific capacity can be attributed to the formation of a solid electrolyte interphase (SEI) layer. The discharge specific capacity decreased continuously during the first seven cycles, then increased after seven cycles, reaching 68 mAh g⁻¹ at 250 cycles. -1 The decrease in discharge specific capacity during the first seven cycles can be attributed to Li. + With fl-Ti3C2T x Irreversible reactions that may occur between various surface functional groups (-OH and -F) on thin films and fl-Ti3C2T x The self-stacking of the material. The continued increase in capacity is likely due to improved lithium-ion accessibility to the active sites during cycling, which is common for electrodes made of two-dimensional nanomaterials. fl-Ti3C2T x The coulombic efficiency of the negative electrode rapidly increased from 55.7% in the first cycle to 99.15% in the tenth cycle, and remained above 99% in subsequent cycles, indicating that fl-Ti3C2T x It exhibits good reversible lithium insertion / extraction behavior. The initial discharge specific capacity of the HPMR-In2O3@C anode (1396 mAh g⁻¹) can be seen in the figure. -1 Similar to HPMR-In2O3@C@Ti3C2T x Microrod (1406mAh g) -1 Furthermore, in the second cycle, the discharge capacity of the HPMR-In2O3@C anode was 822.6 mAh g. -1 HPMR-In2O3@C@Ti3C2T x The discharge capacity of the negative electrode is 780 mAh g. -1The decrease in discharge specific capacity is attributed to the formation of a solid electrolyte interphase (SEI) layer. The discharge specific capacity of HPMR-In₂O₃@C decreased continuously during the first eight cycles, then increased continuously after eight cycles, reaching 1093.1 mAh g⁻¹ at 98 cycles. -1 After that, the specific capacity began to decline continuously. The increase in capacity indicates the gradient activation of the active material, and its hierarchical porous structure is conducive to capturing more lithium ions at the active sites during cycling. After 98 cycles, the specific capacity began to decline, and the battery failed at the 180th cycle. This is because the repeated alloying / dealloying process, accompanied by volume expansion and contraction, caused the negative electrode structure to collapse. HPMR-In2O3@C@Ti3C2T x After a decrease in specific capacity during the first fifteen cycles, it began to gradually increase, reaching 933.6 mAh g after 98 cycles. -1 The concentration was then increased until it reached 1218.7 mAh g after 249 cycles. -1 The increase in specific capacity is also due to the gradient activation of the active material. HPMR-In2O3@C@Ti3C2T x The cycle performance of the Ti3C2T anode material is superior to that of the HPMR-In2O3@C anode material. This is because Ti3C2T x The lamellar structure forms a conductive support layer, leading to the formation of extensive mesopores and macropores in the composite material. These interconnected lamellar pores can adsorb and store more lithium ions through the electric double-layer capacitance mechanism, forming an electrolyte reservoir, shortening the ion diffusion distance, and mitigating volume expansion. Through the study of fl-Ti3C2T... x , HPMR-In2O3@C, HPMR-In2O3@C@Ti3C2T x Rate performance tests of the three anode materials further confirmed the effectiveness of HPMR-In2O3@C@Ti3C2T. x Advantages. At current densities of 0.1C, 0.5C, 1C, 2.5C, 5C, and 10C, fl-Ti3C2T... x The average reversible specific capacities were 52.5, 30.5, 24.5, 19.2, 15.2, and 26.3 mAh g, respectively. -1 When the current density recovers to 0.1C, the reversible specific capacity still reaches 74.8 mAh g. -1 This indicates that fl-Ti3C2T x It exhibits excellent rate performance. The average reversible specific capacities of HPMR-In2O3@C are 813.4, 544.6, 482.2, 402.0, 281.4, and 67.0 mAh g, respectively. -1 When the current density recovers to 0.1C, the reversible specific capacity still reaches 894.8 mAh g. -1This indicates that HPMR-In2O3@C exhibits excellent rate performance. This demonstrates that the carbon framework formed by carbonizing MIL-68(In) effectively mitigates the significant volume change, providing a highly conductive carbon network for charge transfer, thereby improving the rate performance of HPMR-In2O3@C. HPMR-In2O3@C@Ti3C2T x The average reversible specific capacities were 808.4, 554.0, 487.5, 416.7, 340.2 and 214.2 mAh g, respectively. -1 When the current density recovers to 0.1C, the reversible specific capacity still reaches 807.4 mAh g. -1 At a high current density of 10C, HPMR-In2O3@C@Ti3C2T x Compared to HPMR-In2O3@C, the rate performance is more significant, fully demonstrating the superior performance of HPMR-In2O3@C@Ti3C2T. x The outstanding characteristics of Ti3C2T. x The sheet forms an electrolyte reservoir, shortening the ion diffusion distance, and Ti3C2T x It inherently possesses superior electrical conductivity, which enhances the charge transfer rate of the composite material, thereby improving the performance of HPMR-In2O3@C@Ti3C2T. x Rate performance of the anode material. Furthermore, electrochemical impedance spectroscopy (EIS) was used to further test fl-Ti3C2T. x HPMR-In2O3@C@ and HPMR-In2O3@C@Ti3C2T x The dynamic properties.
[0115] from Figure 9c , Figure 9d and Figure 9e It can be seen that all three negative electrode materials exhibit a concave semicircle in the mid-to-high frequency range and a sloping line in the low frequency range. The intercept of the impedance curve with the real axis represents the impedance of the electrolyte. The semicircle is related to the charge transfer resistance at the interface between the negative electrode and the electrolyte; the larger the diameter of the semicircle, the greater the resistance experienced by the electrode material. The sloping line is related to the lithium-ion diffusion resistance within the active material. The sharp decrease in the semicircle of the three negative electrode materials in the mid-to-high frequency range indicates a gradual decrease in charge transfer resistance during the continuous lithium-ion insertion / extraction cycle, thereby improving the electrode conductivity and achieving excellent rate performance. To more clearly illustrate the charge-discharge mechanism of the three electrodes, we disassembled a coin cell after 250 cycles at a current density of 2C, washed the negative electrode in DEC solvent, and dried it. Figures 10a to 10f They are fl-Ti3C2T x HPMR-In2O3@C and HPMR-In2O3@C@Ti3C2T xMorphology of the three types of electrodes before and after cycling. Figure 10a fl-Ti3C2T x Morphological image of the electrode before cycling. Figure 10d fl-Ti3C2T x Morphology of the electrode after cycling. The figure shows that fl-Ti3C2T x The electrode surface was smooth before cycling, but became rough after cycling. This is because lithium is inserted into fl-Ti3C2T. x Caused by the interlayer. Figure 10b This is a morphology image of the HPMR-In2O3@C electrode before cycling. Figure 10e The image shows the morphology of the HPMR-In2O3@C electrode after cycling. As can be seen from the image, HPMR-In2O3@C still exhibits a rod-like structure, indicating that the active material has not collapsed. Figure 10c HPMR-In2O3@C@Ti3C2T x Morphological image of the electrode before cycling. Figure 10f HPMR-In2O3@C@Ti3C2T x Morphology of the electrode after cycling. The figure shows that HPMR-In2O3@C@Ti3C2T x It still exhibits a rod-like structure, indicating that the active material has not collapsed; at the same time, HPMR-In2O3@C@Ti3C2T can be observed. x There is slight expansion. This confirms the presence of HPMR-In2O3@C@Ti3C2T x The characteristics of lithium insertion into Ti3C2T x The lamellar pores allow for more complete redox reactions during charging and discharging.
[0116] This embodiment employs the metal-organic framework (MOF) method, using In(NO3)3·5H2O as the indium source and PTA as the organic ligand, to synthesize the MOF MIL-68(In) via a hydrothermal method. Subsequently, MIL-68(In) is subjected to high-temperature carbonization to prepare a hierarchical porous microrod HPMR-In2O3@C composite material. The MOF method and electrostatic self-assembly method are used to synthesize Ti3C2T... x It is electrostatically self-assembled with MIL-68(In) to form MIL-68(In)@Ti3C2T x Next, MIL-68(In)@Ti3C2T x High-temperature carbonization was used to prepare hierarchical porous microrods HPMR-In2O3@C@Ti3C2T x Composite materials. Few-layer or monolayer Ti3C2T prepared by freeze-drying process. x (fl-Ti3C2T xUsing one material as a control group, the electrochemical performance of the three materials was investigated. The following main conclusions were drawn:
[0117] (1) fl-Ti3C2T x As the negative electrode, fl-Ti3C2T x It mainly relies on capacitors for energy storage. The lithium storage capacity is relatively small, but the cycle stability is good and the rate performance is good.
[0118] (2) HPMR-In2O3@C, as the negative electrode, possesses excellent characteristics such as shortened electron and ion diffusion distance, large specific surface area, abundant active sites, and reserved space for volume changes during cycling. Moreover, the interconnected organic linkers in the MIL-68(In) precursor form a highly intact organic framework. The carbon skeleton formed in situ through carbonization can effectively buffer the huge volume changes of In2O3, while providing a highly conductive network for electron transfer. This is beneficial for stabilizing the SEl film formed on the electrode surface, giving the HPMR-In2O3@C negative electrode high capacity, good cycling performance, and rate performance.
[0119] (3) HPMR-In2O3@C@Ti3C2T x As an anode, the continuous one-dimensional hierarchical porous structure possesses excellent properties such as shortened electron and ion diffusion distances, large specific surface area, abundant active sites, and ample space for volume changes during cycling. The carbon framework formed in situ by MIL-68(In) carbonization can effectively buffer the large volume changes of In2O3 while providing a highly conductive network for electron transfer. Based on this, these interconnected Ti3C2T... x The coating layer, through its lamellar pores and double-layer capacitance mechanism, can adsorb and store more lithium ions, providing a conductive electrolyte reservoir for the internal HPMR-In2O3@C. These structural features enhance the interaction between the electrode and the electrolyte, thereby endowing HPMR-In2O3@C@Ti3C2T with... x The negative electrode exhibits better cycle performance and superior rate performance.
Claims
1. Hierarchical porous microrods In2O3@C@Ti3C2T for lithium-ion battery anodes x A method for preparing composite materials, characterized in that, Includes the following steps: Step (1): Add indium salt and terephthalic acid to N,N-dimethylformamide and stir to mix well to obtain a homogeneous solution; Step (2): Continue heating and maintaining the temperature of the homogeneous solution to obtain mixed reaction system A; Step (3): Maintaining the temperature of the mixed reaction system A in step (2), argon gas is introduced into the mixed reaction system A, and Ti3C2T is added dropwise into the mixed reaction system A at the same time. x After the aqueous dispersion is added dropwise, the mixture is kept at a constant temperature. After the reaction is complete, it is allowed to cool naturally to room temperature to obtain mixed reaction system B. Step (4): After filtering the mixed reaction system B, the solid product obtained is washed with anhydrous ethanol and then vacuum dried to obtain the precursor MIL-68(In)@Ti3C2T. x ; Step (5): Place the precursor MIL-68 (In)@Ti3C2T x The material is placed in a tube furnace and heat-treated under an argon atmosphere. After heat treatment, multi-level porous microrods In2O3@C@Ti3C2T for use as lithium-ion battery anodes are obtained. x Composite materials.
2. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (1), the indium salt is indium nitrate hydrate or indium chloride hydrate; the mass ratio of indium salt to terephthalic acid is 1:2 to 5, the volume mass ratio of N,N-dimethylformamide to terephthalic acid is 90 to 110 mL / g, and the stirring time is 10 to 30 min.
3. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (2), the homogeneous solution is heated to 115-125°C and then kept at that temperature for 30-40 minutes.
4. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (3), the heat preservation temperature is 115-125℃; Ti3C2T x The aqueous dispersion was added dropwise over 5–10 minutes, with an argon gas flow rate of 30–40 mL / min. After the addition was complete, the reaction system contained Ti₃C₂T. x The initial mass ratio of Ti3C2T to the indium salt is 1:9–11; x The mass concentration of the aqueous dispersion is 4–7 wt%; after the addition is complete, continue to keep warm for 30–40 min.
5. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (3), Ti3C2T x The preparation of an aqueous dispersion includes the following steps: Step (3-1): Add lithium fluoride to hydrochloric acid solution, mix well, and then react. After the reaction is complete, a mixed dispersion A is obtained. Step (3-2): Add Ti3AlC2 to the mixed dispersion A in small amounts several times, and continue stirring the reaction. After the stirring reaction is completed, mixed dispersion B is obtained. Step (3-3): After repeatedly centrifuging the mixed dispersion B, wash it with ultrapure water until the pH of the washing solution is 6-6.5 to obtain the mixed dispersion C. Steps (3-4): After treatment, the mixed dispersion C yields Ti3C2T. x Aqueous dispersion.
6. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 5 x A method for preparing composite materials, characterized in that, In steps (3-4), the mixed dispersion C is treated to obtain Ti3C2T. x The method for preparing aqueous dispersions is as follows: The precipitate obtained after filtering the mixed dispersion C was placed in a vacuum drying oven and dried at 40-45°C for 2-3 hours to obtain Ti3C2T. x Powder; finally, Ti3C2T x The powder is redispersed in water to obtain Ti3C2T. x Aqueous dispersion of Ti3C2T x The aqueous dispersion is a multilayer Ti3C2T x Aqueous dispersion; Alternatively, the mixed dispersion C can be repeatedly centrifuged until the upper liquid turns black, yielding mixed dispersion D. Finally, mixed dispersion D is ultrasonicated in an ultrasonic machine with ice packs and then centrifuged. After centrifugation, the upper liquid is taken as Ti3C2T. x Aqueous dispersion of Ti3C2T x The aqueous dispersion is a few-layer / monolayer Ti3C2T x Aqueous dispersion; the method of centrifugal expansion is as follows: after each centrifugation, shake the centrifuge tube until the precipitate is redispersed, and then centrifuge again; the centrifugation conditions for centrifugal expansion are 5000-5500 rpm for 1-1.5 min; the ultrasonic time for mixed dispersion D is 30-35 min, and the centrifugation conditions after ultrasonication are 3500-4000 rpm for 15-20 min.
7. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 5 or 6 x A method for preparing composite materials, characterized in that, In step (3-1), the concentration of hydrochloric acid solution is 9 mol / L; the molar ratio of lithium fluoride to hydrochloric acid in hydrochloric acid solution is 1:3; the reaction temperature is 40-45℃, and the reaction time is 15-25 min. In step (3-2), the total amount of Ti3AlC2 added is in the molar ratio of lithium fluoride in step (3-1) to 1:11-13; Ti3AlC2 is added in 10-15 portions; the stirring speed during the reaction is 450-550 rpm, the temperature of the reaction is 40-45℃, and the reaction time is 48-50 h. In step (3-3), the centrifugation conditions are 3500-4000 rpm for 15-20 min.
8. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (4), an organic filter membrane with a pore size of 0.22 μm is used for vacuum filtration, and the membrane is washed with anhydrous ethanol at least 3 times; the vacuum drying temperature is 55-65℃ and the vacuum drying time is 4-5h.
9. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (5), the heat treatment includes the following two stages: Step (5-1): Increase the temperature from room temperature to 120-130℃ at a rate of 4-6℃ / min, and hold for 2-2.5 hours; Step (5-2): Continue heating at a rate of 4-6℃ / min to 500-510℃ and hold for 2-2.5 hours.
10. The hierarchical porous microrod In2O3@C@Ti3C2T for lithium-ion battery anode as described in claim 1 x A method for preparing composite materials, characterized in that, In step (1), the indium salt is indium nitrate pentahydrate, the mass ratio of indium nitrate pentahydrate to terephthalic acid is 1:3, the volume-to-mass ratio of N,N-dimethylformamide to terephthalic acid is 100 mL / g, and the stirring time is 20 min. In step (2), the homogeneous solution is heated to 120°C and then kept at that temperature for 30 minutes. In step (3), Ti3C2T x The aqueous dispersion was added dropwise over 10 minutes, with an argon gas flow rate of 40 mL / min. After the addition was complete, the reaction system contained Ti3C2T. x The initial mass ratio of Ti3C2T to indium nitrate pentahydrate is 1:10; x The mass concentration of the aqueous dispersion was 7 wt%; after the addition was complete, the mixture was kept at 120℃ for 30 min. Ti3C2T x The preparation of an aqueous dispersion includes the following steps: Step (3-1): Add lithium fluoride to hydrochloric acid solution, mix well and react. After the reaction is completed, a mixed dispersion A is obtained. The concentration of hydrochloric acid solution is 9 mol / L. The molar ratio of lithium fluoride to hydrochloric acid in hydrochloric acid solution is 1:
3. The reaction temperature is 40℃ and the reaction time is 15 min. Step (3-2): Add Ti3AlC2 to the mixed dispersion A in small amounts several times, and continue stirring to react. After the stirring reaction is completed, mixed dispersion B is obtained. The total amount of Ti3AlC2 added is in the molar ratio of lithium fluoride in step (3-1) to 1:
12. Ti3AlC2 is added in 15 portions. The stirring speed during the stirring reaction is 500 rpm, the stirring temperature is 45℃, and the stirring reaction time is 48 h. Step (3-3): After repeatedly centrifuging the mixed dispersion B, wash it with ultrapure water until the pH of the washing solution is 6 to obtain the mixed dispersion C; the centrifugation conditions are 3500 rpm and 15 min. Steps (3-4): The mixed dispersion C is repeatedly centrifuged until the upper layer turns black, yielding mixed dispersion D. Finally, mixed dispersion D is ultrasonicated in an ultrasonic machine with ice packs and then centrifuged. After centrifugation, the upper layer is taken as Ti3C2T. x Aqueous dispersion; the method of centrifugal expansion is as follows: after each centrifugation, shake the centrifuge tube until the precipitate is redispersed, and then centrifuge again; the centrifugation conditions for centrifugal expansion are 5000 rpm for 1 min; the ultrasonic time for mixed dispersion D is 30 min, and the centrifugation conditions after ultrasonication are 3500 rpm for 15 min. In step (4), an organic filter membrane with a pore size of 0.22 μm was used for vacuum filtration, and the membrane was washed three times with anhydrous ethanol. The vacuum drying temperature was 60℃ and the vacuum drying time was 4 h. In step (5), the heat treatment includes the following two stages: Step (5-1): Increase the temperature from room temperature to 120℃ at a rate of 5℃ / min and hold for 2 hours; Step (5-2): Continue heating to 500℃ at a heating rate of 5℃ / min and hold for 2 hours.
Citation Information
Patent Citations
Preparation method of titanium carbide composite indium-zinc sulfide photo-anode
CN110735151A
Difunctional modified diaphragm for lithium-sulfur battery and preparation method of difunctional modified diaphragm
CN115207567A